2008
DOI: 10.1245/s10434-008-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy by 3-MA Enhances the Effect of 5-FU-Induced Apoptosis in Colon Cancer Cells

Abstract: Our results suggest that 5-FU-induced apoptosis in colon cancer cells can be enhanced by the inhibitor of autophagy, 3-MA. Autophagy might play a role as a self-defense mechanism in 5-FU-treated colon cancer cells, and its inhibition could be a promising strategy for the adjuvant chemotherapy of colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(186 citation statements)
references
References 34 publications
8
175
0
2
Order By: Relevance
“…17,18 A series of studies reported that chemotherapy induced-autophagy promotes the survival of some kinds of cancer cell lines. [19][20][21][22][23] These results suggest that autophagy might be involved in the development of chemotherapy resistance. But few studies on the relationship between autophagy and chemotherapy were reported, especially studies utilizing resistant cancer cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 86%
“…17,18 A series of studies reported that chemotherapy induced-autophagy promotes the survival of some kinds of cancer cell lines. [19][20][21][22][23] These results suggest that autophagy might be involved in the development of chemotherapy resistance. But few studies on the relationship between autophagy and chemotherapy were reported, especially studies utilizing resistant cancer cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 86%
“…Numerous studies have demonstrated that autophagy combats numerous types of adverse stresses and maintains the survival of tumor cells (Li et al, 2009;Carew et al, 2012). Cytotoxic stress and metabolic stress such as hypoxia, nutrition deficiency, chemotherapy, and radiotherapy are common in tumor cells because of their high proliferative activity and high metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In some studies, autophagy and apoptosis have been found to exert similar levels of toxicity 7,8 while in others a blockade to protective autophagy has resulted in cytotoxicity due to apoptosis. 3,[9][10][11][12] Finally, a recent report presents evidence for apoptosis that is dependent on prior autophagy. The transient arrest and renewed tumor growth that has been interpreted as tumor dormancy by Lu et al 2 is also a common observation in other xenograft models treated with chemotherapy or radiation; 19,20 our own studies in cell culture [21][22][23] also support the concept of drug and radiation induced senescence in tumor cells that is succeeded by proliferative recovery.…”
Section: Cytoprotective and Cytotoxic Functions Of Autophagymentioning
confidence: 96%